Asymptotic behavior for delayed backward stochastic differential equations - Manga, Clément; Aman, Auguste; Tuo, Navègué (Communications in statistics. Simulation and computation, 2025)
This paper is devoted to study the asymptotic properties for the solution of decoupled forward backward stochastic differential equations with delayed generators. As an application, we establish a large deviation principe for solution of the backward equations.